489 The Role of Sentinel Lymph Node Biopsy in Cutaneous Head and Neck Melanoma: A Systematic Review and Meta-Analysis. (4th May 2021) - Johnston, E; Taylor, S; Bannon, F; McAllister, S
Abstract: Introduction: : and: : Aims: : The aim of this systematic review is to provide an up-to-date evaluation of the role and test performance of sentinel lymph node biopsy (SLNB) in the head and neck. Method: This review follows the PRISMA guidelines. Database searches for MEDLINE and EMBASE were constructed to retrieve human studies published between 1st January 2010 and 1st July 2020 assessing the role and accuracy of sentinel lymph node biopsy in cutaneous malignant melanoma of the head and neck. Articles were independently screened by two reviewers and critically appraised using the MINORS criteria. The primary outcomes consisted of the sentinel node identification rate and test-performance measures, including the false-negative rate and the posttest probability negative. Results: A total of 27 studies, including 4688 patients, met the eligibility criteria. Statistical analysis produced weighted summary estimates for the sentinel node identification rate of 97.3% (95% CI, 95.9% to 98.6%), the false-negative rate of 21.3% (95% CI, 17.0% to 25.4%) and the posttest probability negative of 4.8% (95% CI, 3.9% to 5.8%). Discussion: : Sentinel lymph node biopsy is accurate and feasible in the head and neck. Despite technical improvements in localisation techniques, the false negative rate remains disproportionately higher than for melanoma in other anatomical sites.